Analisis manajemen hubungan sekolah dengan masyarakat di SD Negeri Kartodipuran Surakarta - Cantika Oktaviana; Aprila Ristania; Sri Marmoah (Universitas Sebelas Maret, 2025)
This research examines the management of school relations with the community at SDN Kartodipuran. The focus of this research is to find out the type of school relations with the community. The purpose of this study is to describe the management of school relations with the community and the functions of planning, implementation and evaluation in management at SDN Kartodipuran. This research approach is qualitative with a descriptive approach. The data source in this research is the principal. Data collection techniques through interviews, observation and documentation. Data analysis through data collection, data reduction, data presentation and conclusion drawing. The results of this study indicate that the types of school and community relations management in an effort to improve the quality of education at SDN Kartodipuran include educational relations, namely with the school committee and institutional relations, namely with the Jayengan Health Center, PLA Surakarta, the police, and the business world. In addition, the management of school and community relations at SDN Kartodipuran also carries out the functions of planning, implementation and evaluation.